Understanding Turkey Management in the Mimbres Valley of Southwestern New Mexico Using Ancient Mitochondrial DNA and Stable Isotopes. Issue 1 (January 2023) - Dolan, Sean G.; Ozga, Andrew T.; Laumbach, Karl W.; Krigbaum, John; Manin, Aurélie; Schwartz, Christopher W.; Stone, Anne C.; Knudson, Kelly J.
Abstract: In the US Southwest and Northwest Mexico, people and turkeys ( Meleagris gallopavo ) have had a reciprocal relationship for millennia; turkeys supplied feathers, meat, and other resources, whereas people provided food, shelter, and care. To investigate how turkeys fit within subsistence, economic production, sociopolitical organization, and religious and ritual practice in the Mimbres Valley of southwestern New Mexico, we report on genetic (mtDNA) and stable isotope (δ 13 C, δ 15 N) data from turkeys recovered from Mimbres Classic period (AD 1000–1130) sites. Results indicate that Mimbres aviculturists had haplogroup H1 and H2 turkeys, and most ate maize-based diets similar to humans, but some ate nonmaize and mixed diets. We contextualize these data to other turkey studies from the northern Southwest and discuss how the human-turkey relationship began, the evidence for pens and restricting turkey movement, and the socioecological factors related to turkey management during the Classic period, particularly the challenges associated with providing maize to turkeys during times of environmental stress. This study has broad relevance to places where people managed wild, tame, and domestic animals, and we offer new insights into how prehispanic, small-scale, middle-range agricultural societies managed turkeys for ritual and utilitarian purposes.